Following Students' Suggestions for Rewriting a Computer Programming Textbook. - Pepper, Jeff (American Educational Research Journal)
This paper discusses the results of two experiments in technical text-book design. In the first experiment, excerpts from two existing computer programming texts were given to a group of college students. Comprehension of both texts was found to be poor. and surprisingly, the subjects overwhelmingly preferred a verbose and poorly written text over a concise and well written one. It was concluded from the students' comments that they were looking for an easy-to-read text with lots of examples. A chapter was written in this style, and it was found that the students' comprehension improved substantially, and they also liked the new "text" much better than any of the others.